Architectural Criticism as A Tool in Defining Environmental Aesthetic - Irina Mildawani; Muhammad Farhan Ghazy (Journal of Architecture & Environment, 2022)
The attractiveness of physical settings covers from its initial concentration on ordinary settings to anthropogenic environments, including the beauty of everyday life in the late twentieth century. A mosque is a place of worship that tends to be influenced by the legacy of glorious Islamic civilization in Indonesia. The current modern architectural design shows the existence of environmental aesthetics and local culture without losing the essence of the mosque as a place of worship. This study aims to determine the public's perception of architectural criticism of mosques with unique designs based on modernity and local culture. The method used is a descriptive case study scrutinizing respondents' perceptions in criticizing the mosque building through online questionnaires. Twenty respondents with an architectural background and 20 without architectural knowledge were chosen to answer Likert scale-based questions. The questions refer to three architectural aspects: symbols or characters, attractiveness, and functionality of the mosque. The results showed that respondents with architectural education background dominantly perceived an eminent consensus on the three architectural features compared to the ones of non-architectural environment. This indicates that respondents with an architectural education background understood the symbolic facet of the setting's attractiveness of mosque better when viewed from architectural criticism's point of view.